The influence of irrigation methods on the water regime and productivity of greenhouse tomatoes - G. M. Mustafaev; A. A. Magomedova; S. M. Mursalov; A. Ch. Sapukova; M. M. Khalikov (Овощи России)
Relevance. The water regime is one of the main processes in the life of the plant, optimizing which can increase the yield of cultivated crops. In protected ground conditions, the plants' water needs are met exclusively by irrigation. Irrigation is the most important means of increasing the yield of greenhouse crops, including tomato. Greenhouse tomatoes are very demanding on soil moisture, as well as on air humidity. To combat overheating of the air and plants, and to increase the relative humidity of the air in greenhouses, plants for evaporative cooling and humidification of plants are successfully used, which are especially effective in drip irrigation. The combination of drip irrigation with evaporative cooling makes it possible to control the water regime of the soil and air habitat of plants.Materials and Methods. The purpose of the research: to identify the most optimal method of water supply for greenhouse tomatoes. The research was conducted in 2018-2019 in the greenhouse complex "Yugagroholding", located in the suburbs of the city of Makhachkala. The object of research was a hybrid of tomato Mei shuai. The experiments included three options: sprinkling, drip irrigation, and drip irrigation with evaporative cooling.Results. The comparative characteristics of irrigation methods by yield are presented, the results of which indicate the advantage of the second and third options over sprinkling: the highest yield was obtained in the third option and amounted to 14.7 kg/m2 . The best methods of water supply that ensure the optimal water regime of greenhouse tomatoes are identified-drip irrigation and drip irrigation in combination with evaporative cooling, the latter is the best in most indicators.